Revan Indices of Oxide and Honeycomb Networks - V. R. Kulli (International Journal of Mathematics And its Applications, 2017)
There are many types of topological indices. Among degree based topological indices, Zagreb indices, Banhatti indices, Gourava indices are studied well. In this paper, we introduce the Revan indices and compute exact formulas for oxide and honeycomb networks.